Does economic development and democracy translate to happiness? a global perspective - V. Rasiah, R. Ratneswary; Thuraisingam, Ambikai S.; Jambulingam, Manimekalai; Habibullah, Muzafar Shah (American-Eurasian Network for Scientific Information, 2013)
This paper explores the relatively intriguing area of research on the “economics of happiness”. The present study was designed to determine the effects of economic development and democratic freedom on happiness. A cross-sectional econometric analysis is employed to examine the impact of the economic variables of income and democracy on happiness across thirty eight countries in 2011. Democracy and economic development were found to contribute positively to happiness. The findings also indicate a bi-directional relationship between happiness and its dual determinants of income and democratic freedom. It was found that countries reporting higher levels of well-being tend to enjoy higher incomes and seem to choose democracy over other political overtures. Institutions of democracy were found to enhance economic development and this relationship is bi-directional. The study concludes with an examination of policy implications of the findings.